The Effects of User Interface Design for Mobile Learning Application on Learner's Extraneous Cognitive Load: A Conceptual Framework - Faudzi M.A.; Cob Z.C.; Sharudin S.A.; Omar R.; Ghazali M. (Association for Computing Machinery, 2024)
In today's fast-paced society, when learning can take place anytime and anywhere, mobile learning is extremely relevant. Nonetheless, despite these significant benefits, there are numerous problems that could slow down the learning process. Due to the small screen size and user interface that are inappropriately designed for mobile devices, learners are experiencing an increase in their cognitive load. This study examines the relationships between mobile learning user interface design and their effects on learners' cognitive load, specifically the extraneous load. First, the mobile learning user interface design criteria that affect the learner's cognitive load are identified. Next, a study on cognitive load measurement is implemented to further understand the type, method and criteria of cognitive load. Both of these findings are important in understanding the relationship between the mobile learning user interface design and learner's cognitive load. This study presented a conceptual framework for the effects of user interface design for mobile learning application on learner's extraneous cognitive load. This conceptual framework will be the foundation of a user interface design framework that aims at improving learner's cognitive load when implementing mobile learning apps. This framework will offer guidance for those interested in designing mobile learning applications, that give learners an effective knowledge and mobile learning experience, hence improving the success of the mobile learning process. 2023 ACM.